2007
DOI: 10.1101/gad.1499407
|View full text |Cite
|
Sign up to set email alerts
|

pRB family proteins are required for H3K27 trimethylation and Polycomb repression complexes binding to and silencing p16INK4a tumor suppressor gene

Abstract: Genetic studies have demonstrated that Bmi1 promotes cell proliferation and stem cell self-renewal with a correlative decrease of p16INK4a expression. Here, we demonstrate that Polycomb genes EZH2 and BMI1 repress p16 expression in human and mouse primary cells, but not in cells deficient for pRB protein function. The p16 locus is H3K27-methylated and bound by BMI1, RING2, and SUZ12. Inactivation of pRB family proteins abolishes H3K27 methylation and disrupts BMI1, RING2, and SUZ12 binding to the p16 locus. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
292
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(305 citation statements)
references
References 22 publications
11
292
2
Order By: Relevance
“…The neural stem cell defect can be partially rescued by disruption of the Ink4a-Arf locus (Molofsky et al, 2005). Although Bmi1 has been shown by chromatin immunoprecipitation to be present at the promoters of p16 INK4a and p19 ARF (Bracken et al, 2007;Kotake et al, 2007), Bmi1 is unable to directly bind to DNA in a sequence-specific manner (Tagawa et al, 1990;Alkema et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neural stem cell defect can be partially rescued by disruption of the Ink4a-Arf locus (Molofsky et al, 2005). Although Bmi1 has been shown by chromatin immunoprecipitation to be present at the promoters of p16 INK4a and p19 ARF (Bracken et al, 2007;Kotake et al, 2007), Bmi1 is unable to directly bind to DNA in a sequence-specific manner (Tagawa et al, 1990;Alkema et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that repression of Hox genes and other key developmental regulators is established in embryonic stem (ES) cells (Boyer et al, 2006). Thus, we used murine ES cells to perform chromatin immunoprecipitation on four genes, HoxA7, HoxA10, HoxA11, and Arf, which have previously been shown to be directly regulated by Bmi1 (Cao et al, 2005;Bracken et al, 2007;Kotake et al, 2007;Xi et al, 2007). We found that Bmi1 was directly bound to the promoters of HoxA7, HoxA10, HoxAll, and Arf in mouse embryonic stem cells (Fig.…”
Section: Bmi1 and E2f6 Synergize In Axial Skeleton Development And Comentioning
confidence: 95%
“…One possibility is that PcGinteracting proteins facilitate PRC2 targeting. Interestingly, the tumor suppressor Retinoblastoma protein (Rb) is necessary to maintain H3K27 methylation and PRC2 and PRC1 binding to the promoter of the CDK inhibitor p16 in human cells (Kotake et al, 2007). The plant homolog of human Rb, the RETINOBLASTOMA-RE-LATED (RBR) protein, binds to FIE (Mosquna et al, 2004) and MSI1 (Ach et al, 1997;Rossi et al, 2001).…”
Section: Histone Methylasesmentioning
confidence: 99%
“…Their oncogenic potential is mainly mediated through PcG-mediated H3K27 methylation and epigenetic inactivation of the INK4A-ARF locus. 39,40 The INK4A-ARF locus encodes tumor suppressor genes p16 INK4A and p14 ARF , which are key regulators of cellular senescence.…”
Section: Jmjd3/kdm6bmentioning
confidence: 99%